Entamoeba Histolytica ve Ürtiker - Kurtuluş Aksu (Ankara Medical Journal, 2016)
Dear Editor,I have read the article “Chronic spontaneous urticaria and internal parasites–a systematic review” written by Kolkhir P et al published in Allergy with great interest and benefited information regarding possible relationship between parasitic infections and chronic spontaneous urticaria in Turkey.1 In this article it is mentioned that Blastocystishominis and Giardia spp are related to chronic spontaneous urticaria (CSU) in Turkey. Entamoeba histolytica, on the contrary, is blamed to be responsible for this pathology only in one report from India. As mentioned in this article, Entamoeba histolytica, which is the third most common cause of parasitic infections, is the most common cause of CSU in adults. We have recently published a report on coexistence of urticaria and Entamoeba histolytica in your journal.2 Among 188 patients diagnosed with urticaria in our Immunology and Allergy Clinic between July 2013 and April 2014, routine microscopic stool examinations revealed positive results in four specimens. These four specimens were positive for Entamoeba histolytica resulting in an incidence of 2.1%.In this context, we think that parasitic infections should be concerned in all patients with CSU; however, this issue should be evaluated more closely and responsible microorganisms as to the basis of countries should be investigated with epidemiological studies.